Generation of quantum codes using up and down link optical soliton - Amiri, I. S. (Penerbit UTM Press, 2011)
In this study, a system of continuous variable quantum code via a wavelength router is presented. The optical Kerr type nonlinearity in the nonlinear microring resonator (NMRR) induces the chaotic behavior. In this proposed system chaotic signals are generated by an optical soliton or Gaussian pulse within a NMRR system. Large bandwidth signals of optical soliton are generated by the input pulse propagating within the MRRs, which is allowed to form the continuous wavelength or frequency with large tunable channel capacity. Therefore, distinguished up and down links of wavelength or frequency pulses can be generated by using localized spatial soliton via a quantum router and networks. These selected up and down links pulses are more suitable to generate high secured quantum codes because of the greater free spectral range (FSR). The continuous quantum codes can be generated by using the polarization control unit and beam splitter, incorporating into the MRRs. In this work, frequency band of 10.7 MHz and 16 MHz and wavelengths of 206.9 nm, 1.448 µm, 2.169 µm and 2.489 µm can be obtained for QKD by using input optical soliton and Gaussian beam.